2014
DOI: 10.9734/bjmmr/2014/11147
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fasting Glucose & 8-Iso-Prostaglandin F2α in Diabetes Disease Progression

Abstract: Aims: The objective of the present study was to evaluate the changes of 8-isoprostaglandin F 2α and other markers of oxidative stress with impaired fasting glucose when compared to non-diabetic control participants. Methodology: This is a cross-sectional study, conducted at Charles Sturt University, Albury, NSW, Australia and included 428 participants (female: male, 247:181) participants attending the Diabetes Complications Clinic in the School of Community Health for the period between January 2011 to October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…A clinical study performed by Bandeira and coworkers [36] was demonstrated in diabetic patients of our study and a significant association was recorded with 8-iso-PGF2α. Serum lipids showed significant elevation in diabetic patients (p < 0.0001) but in HDL-C, a significant decrease (p = 0.04) was recorded confirming other reports [32] demonstrated a significant reduction in both total cholesterol and HDL-C which explains the increased 8-iso-PGF2α as HDL-C caries 8-iso-PGF2α [10].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A clinical study performed by Bandeira and coworkers [36] was demonstrated in diabetic patients of our study and a significant association was recorded with 8-iso-PGF2α. Serum lipids showed significant elevation in diabetic patients (p < 0.0001) but in HDL-C, a significant decrease (p = 0.04) was recorded confirming other reports [32] demonstrated a significant reduction in both total cholesterol and HDL-C which explains the increased 8-iso-PGF2α as HDL-C caries 8-iso-PGF2α [10].…”
Section: Discussionsupporting
confidence: 83%
“…Jelinek et al [32] demonstrated a significant increase in 8-iso-PGF2α in the IFG group and supports the findings that, 8-iso-PGF2α was increased following an oral glucose tolerance in individuals with no diabetes but with either IFG or impaired glucose tolerance [33]. 8-iso-PGF2α was elevated in the sera of diabetic patients (2719.38 ± 1864.68 pg/ml) in current study compared with non-diabetic control (951.45 ± 669.44 pg/ml, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…19.4% of the control group used statins compared with 37.5% of the IFG group." Another study using a sample of the DiScRi data actually acknowledges the TC level reduction: [62] "Both total cholesterol and HDL-C were significantly lower in the IFG group, while triglycerides and LDL-C showed no difference between the groups." It was also noted that ".…”
Section: Cholesterol Profiles and Lipid Lowering Drugsmentioning
confidence: 99%
“…Urinary excretion of 8-iso-PGF 2 α has been found to be higher in hypertensive and diabetic patients when compared to healthy controls. 16 , 20 The increase in urinary 8-iso-PGF 2 α is associated with elevation of serum total cholesterol (TC) and reduction of high-density lipoprotein cholesterol (HDL-C) that can lead to atherosclerosis and coronary heart disease. 20 Hypertensive and normotensive diabetic patients have similar urinary 8-iso-PGF 2 α excretion, suggesting similar mechanisms with respect to glycemic control, lipid peroxidation, and antioxidation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 20 The increase in urinary 8-iso-PGF 2 α is associated with elevation of serum total cholesterol (TC) and reduction of high-density lipoprotein cholesterol (HDL-C) that can lead to atherosclerosis and coronary heart disease. 20 Hypertensive and normotensive diabetic patients have similar urinary 8-iso-PGF 2 α excretion, suggesting similar mechanisms with respect to glycemic control, lipid peroxidation, and antioxidation mechanisms. 21 , 22 Atherosclerosis is associated with HTN and is characterized by oxidative stress and pro-inflammatory activity that may be associated with the observed imbalance between coagulation and fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%